The impact of interpretive and reductive front-of-pack labels on food choice and willingness to pay - Talati, Zenobia; Norman, Richard; Pettigrew, Simone; Neal, B.; Kelly, B.; Dixon, H.; Ball, K.; Miller, C.; Shilton, Trevor (Biomed Central, 2017)
© 2017 The Author(s). Background: This study examined how front-of-pack labels and product healthfulness affect choice and willingness to pay across a range of foods. It was hypothesized that: (i) product choice and (ii) willingness to pay would be more aligned with product healthfulness when healthfulness was expressed through the Health Star Rating, followed by the Multiple Traffic Light, then the Daily Intake Guide, and (iii) the Nutrition Facts Panel would be viewed infrequently. Methods: Adults and children aged 10+ years (n = 2069) completed an online discrete choice task involving mock food packages. A 4 food type (cookies, corn flakes, pizza, yoghurt) × 2 front-of-pack label presence (present, absent) × 3 front-of-pack label type (Daily Intake Guide, Multiple Traffic Light, Health Star Rating) × 3 price (cheap, moderate, expensive) × 3 healthfulness (less healthy, moderately healthy, healthier) design was used. A 30 s time limit was imposed for each choice. Results: Of the three front-of-pack labels tested, the Health Star Rating produced the largest differences in choices, with 40% (95% CIs: 38%-42%) of respondents selecting the healthier variant, 33% selecting the moderately healthy variant (95% CIs: 31%-35%), and 23% (95% CIs: 21%-24%) selecting the less healthy variant of the four products included in the study. The Multiple Traffic Light led to significant differences in choices between healthier (35%, 95% CIs: 33%-37%) and less healthy products (29%, 95% CIs: 27%-31%), but not moderately healthy products (32%, 95% CIs: 30%-34%). No significant differences in choices were observed by product healthfulness when the Daily Intake Guide was present. Only the Health Star Rating resulted in a significantly greater willingness to pay for healthier versus less healthy products. The Nutrition Facts Panel was viewed for only 7% of all mock packages. Conclusions: Front-of-pack labels that are more interpretive, such as the Health Star Rating, can be more effective at directing consumers towards healthier choices than reductive front-of-pack labels such as the Daily Intake Guide. The study results provide policy makers with clear guidance on the types of front-of-pack labels that are most likely to achieve positive health outcomes at a population level.